PENGARUH ULASAN PELANGGAN ONLINE DAN IKLAN TERHADAP MINAT BELI PADA PENGGUNA APLIKASI TIKTOK DI DKI JAKARTA - Jesslyn Jesslyn; Salam Fadillah Alzah; Serpian Serpian; Ai Heni Novianti (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2023)
Technology is a community need, knowing that the internet can help people in many ways such as connectivity and a very wide range, reducing communication costs, interaction, flexibility, and being able to spread knowledge quickly and easily for online transactions. The theory used in this research is Online Customer Reviews, Advertising and Purchase Intention. The variables in this study are divided into two types, namely the independent variable and the dependent variable. The independent variables in this study are Online Customer Reviews and Advertising, while the dependent variable in this study is Purchase Interest. Data was collected by distributing questionnaires to 112 respondents in the sample of TikTok consumers in DKI Jakarta. Sampling was done by purposive sampling. The analytical methods used include Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Regression Analysis Test, T Test and F Test. The test was carried out using the help of SPSS 26. The conclusion of this study is that the results of the data show that there is an effect of online customer reviews on Purchase Intention while advertising is not affected by Purchase Intention.